2008
DOI: 10.1002/jcu.20418
|View full text |Cite
|
Sign up to set email alerts
|

Breast filariasis: Real‐time sonographic imaging of the filarial dance

Abstract: A 50-year-old woman presented with a palpable tender nodule in the upper quadrant of the breast that was clinically thought to be a fibroadenoma, with mammographic findings of a well-defined lobulated density. Sonographic examination revealed a "filarial dance sign" within the cystic lesion, which is diagnostic of lymphatic breast filariasis. In endemic areas, sonographic examination is recommended to search for this pathognomonic real-time diagnostic feature and, if present, to initiate treatment without dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
(7 reference statements)
2
5
0
Order By: Relevance
“…This was confirmed on cytologic examination of the aspirate. These findings were similar to those of Surendrababu et al ( 10 ).…”
Section: Discussionsupporting
confidence: 93%
“…This was confirmed on cytologic examination of the aspirate. These findings were similar to those of Surendrababu et al ( 10 ).…”
Section: Discussionsupporting
confidence: 93%
“…Literature review revealed incidental diagnosis of filarial infestation of female genital tract . Worm nests have been found in the breast, thigh, calf, scrotum, and inguinal nodes …”
Section: Discussionmentioning
confidence: 99%
“…Literature review revealed incidental diagnosis of filarial infestation of female genital tract. 1,2 Worm nests have been found in the breast, 3 thigh, calf, scrotum, 4 and inguinal nodes. 5 The FDS seen in distended lymphatics is characteristic of filarial infestation.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few protozoans such as trichomonas and echinococcus and nematodes like filaria can involve the breast, resulting in mostly cystic lesions. 10,11 Only one case with a solid mass caused by protozoan has been reported so far. In that case, the parasitic agent was leishmania and the diagnosis was achieved by a fine-needle aspiration biopsy.…”
Section: Discussionmentioning
confidence: 99%